Critical practices in international theory [ selected essays - Der Derian, James (Routledge, 2009)
Contains essays that cover a variety of issues including diplomacy, alienation, terrorism, intelligence, national security, various forms of warfare, the role of information technology in international relations, poststructuralist theory, and the military-entertainment-media matrix